Long-term 3D culture of the SCC4 cell line using three different culture methods and initial seeding densities - Rustamov, Valeh; Rudolf, Rüdiger; Yagublu, Vugar; Kuhn, Hella-Monika; Vitacolonna, Mario; Hafner, Mathias (Journal of cellular biotechnology, 2017)
INTRODUCTION: In recent years, many different methods were introduced for generation of 3D cell culture. However, many currently available three-dimensional techniques are not suitable for certain cell lines and sometimes showed a lack of reproducibi